El papel de Granada en las relaciones castellano-portuguesas (1369-1492) - López de Coca Castañer, José Enrique (Espacio Tiempo y Forma. Serie III, Historia Medieval, 2004)
Temor de Castilla a una alianza entre Portugal y la Granada musulmana. La casa de Avis aspira a tomar parte en la conquista del emirato nazarí. Papel que desempeña el infante don Enrique en todo esto. Castellanos y portugueses colaboran en la defensa de Ceuta y otras plazas fuertes contra los ataques de granadinos y marroquíes. Fear of Castile to an alliance between Portugal and Moslem Granada. The House of Avis long for taking part in the conquest of the Nasri kingdom. The role of prince D. Enrique in this business. Castilians and Portuguese collaborate in the defence of Ceuta and other strongholds against the attacks of natives of Granada and Moroccans.